MUNÂSABAH BETWEEN CHAPTERS ON QUR’AN IN THE AL-BIQÂ’Î PERSPECTIVE - Ahmad Zainal Abidin; Ahmad Saddad (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
The Study on munāsabah occupies an important position in the study of the Koran. Al-Biqā'î is one of the scholars who give a very large portion of the theory of munāsabah. Al-Biqā'î divides munāsabah into two major groups, namely, between surah (chapters) and between ayat (verses). With an exploratory-descriptive method, this paper will specifically explore logical pattern of munāsabah between surah according to al-Biqa'i with a comprehensive example. The findings of this paper are based on: first, there are four possible patterns of munāsabah between surah according to al-Biqa'i. The four patterns are munāsabah between surah’ names and its content, munāsabah between surah and basmalah, munāsabah between the initial description of the surahs and munāsabah between the end of the surah and the other surah. Second, al-Biqa'i in applying a munāsabah theory is quite consistent across patterns; from the first, second, third, and fourth patterns. Third, Munāsabah occupies a very important position because it is able to explain the unity and close relationship that exists between one surah and another while also emphasize the oneness of the Qur'anic themes.